Prototype Sistem Pemantauan Keamanan Melalui Jaringan Internet Menggunakan Android - Rahman, Adik Surya Fauzi, Bana Handaga, S.T.,M.T.,P.h.D (2016)
Theft crime makes citizens very nervous, especially in urban areas. There are many ways you can do to avoid the crime of theft in the home or office, such as security pertugas hire private security guards to keep watch. Of course this will add to expenses per month. Often we see the incidence of theft of home or office entrance through doors and windows, to track the window can be treated using iron trailis, while for the door track a bit difficult because of the width of the door is too big and is the main access entrance and exit of people. It required an automatic door system and can be monitored remotely using the Android app. In pengaplikasianya the system uses Finggerprint as the door lock which will give access to people who are already registered fingerprints. The system is run by using arduino based applications that will work to open the door with the reading of the fingerprint data has been registered, as well as Android devices that will receive notifications if the door has been opened. Given such a security system homeowners will feel safe as any people can get into the house. With the implementation of these security systems do not require a key user manual or electric locking bermedia remote to conduct open the door. Penerepan fingerprint only limited to the Windows XP operating system.